The Effect of Paternal Incarceration on Material Hardship - Schwartz-Soicher, Ofira (2011)
High rates of incarceration among American men, coupled with a high prevalence of fatherhood among the incarcerated, have led to millions of children and families whose fathers are, or have been, in the nation’s jails and prisons. This study uses data from the Fragile Families and Child Wellbeing Survey to estimate the extent to which paternal incarceration increases family material hardship. Analyses from a series of longitudinal regression models suggest that material hardship is statistically significant and positively associated with paternal incarceration. These hardships are found to reflect not only a reduction in fathers’ income and financial contributions but also an increase in financial and other family strains. The findings underscore the challenges facing families with incarcerated fathers. They also emphasize the need for efforts by criminal justice agencies and social service providers to help mitigate the risks associated with paternal incarceration.